2022
DOI: 10.1007/s13364-022-00634-6
|View full text |Cite
|
Sign up to set email alerts
|

Density and occupancy of leopard cats across different forest types in Cambodia

Abstract: The leopard cat (Prionailurus bengalensis) is the most common wild felid in Southeast Asia, yet little is known about the factors that affect their population density and occupancy in natural habitats. Although leopard cats are highly adaptable and reportedly can attain high densities in human-modified habitats, it is not clear which natural habitat is optimal for the species. Also, this felid has been preyed upon by large carnivores in Southeast Asia, yet the intra-guild effects of large carnivore presence on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…For example, Pin et al. (2022) found higher sex ratios for female leopard cats ( Prionailurus bengalensis ) in three different study areas within Cambodia (1.2–1.9:1 females/males) using SECR models. Similar to our study, ocelot sex ratios in Misiones, Argentina, were higher for females at two sites (0.67:1 and 0.45:1 males/females; Di Bitetti et al., 2006).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Pin et al. (2022) found higher sex ratios for female leopard cats ( Prionailurus bengalensis ) in three different study areas within Cambodia (1.2–1.9:1 females/males) using SECR models. Similar to our study, ocelot sex ratios in Misiones, Argentina, were higher for females at two sites (0.67:1 and 0.45:1 males/females; Di Bitetti et al., 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of modern environmental gradients, the habitat associations we describe are limited to areas with predominantly tropical rainforests where the preponderance of our sampling occurred. However, in predominantly dry evergreen and deciduous forests in northern Thailand and evergreen‐deciduous mosaics in Cambodia, Petersen et al (2019) and Pin et al (2022) found that leopard cats had higher densities in intact than regenerating forests and in more evergreen than deciduous forests, respectively. When considering prior work in context with our MaxEnt SDMs, landscape‐ and local‐scale analyses, leopard cats appear to show a regional preference for drier lowland habitats, including interior forests, while in rainforests they shift to being comparatively edge and disturbance specialists.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, leopard cat occurred in temperate to sub-alpine forests (>3,000 m, moderate slope) ( Mishra, Madhusudan & Datta, 2006 ; Thapa et al, 2013 ; Irawan et al, 2020 ). Leopard cats prefer rugged terrain, tree-covered (high NDVI), and woodland habitats ( Ghimirey & Ghimire, 2010 ; Bashir et al, 2014 ; Buzzard, Li & Bleisch, 2018 ; Pin et al, 2022 ) in natural forests. It used lower reaches and a wide range of habitats in anthropogenic sites ( Lorica & Heaney, 2013 ; Petersen et al, 2019 ; Wu et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%